La legge Ossicini, ovvero come fu che la psicoterapia italiana si allontanò dalla medicina - Testa, Luana; Del Missier, Giovanni (Il sogno della farfalla, 2012)
The Authors retrace the twenty-year long parliamentary procedure that led to the passing of Law 56/89 which set up a Psychologists’ Register in Italy and regulated psychotherapeutic activity one hundred years after the term’s first official appearance. The law, better known as Law Ossicini after its author, whose brief biography is offered in this article, has given rise to some degree of controversy which still persists. In particular, the legitimacy of Article 3 of the Law which regulates psychotherapy is still being debated, as is the validity of the training courses devised by the various private psychotherapy schools as a result of the Law. The Authors end the historical excursus with a personal criticism of the cultural implications of the Law which having placed psychotherapy apart from medicine interrupted the process of integrating psychology within medicine, a process which had started in the second half of the 1800s. Psychiatry then ended up embracing organicism and psychotherapy was deprived of a medical approach.